Pengaruh Return On Assets dan Earning Per Share Terhadap Harga Saham Pada PT. Hanjaya Mandala Sampoerna Tbk - Ridwan, Naufalia; Sunrawali, Andi Nonong (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2025)
Stock prices reflect a company’s value; when a company achieves good performance, its shares tend to attract many investors. The higher the company’s value, the higher its stock price. Company valuation is generally assessed through its financial performance. This study employs descriptive analysis using Return on Assets (ROA) and Earnings Per Share (EPS) to obtain an overview of the financial statements of PT Hanjaya Mandala Sampoerna, Tbk. Furthermore, multiple linear regression statistical analysis is used to examine the effect of Return on Assets and Earnings Per Share on stock prices. The results of the study yield the regression equation Y = −1,524.25 + 177.74X₁ + 0.18X₂, with a coefficient of determination (R²) of 0.8810 or 88.10%, and a correlation coefficient (r) of 0.9386, indicating a very strong relationship between the independent variables and the dependent variable. The findings show that Return on Assets and Earnings Per Share simultaneously have a significant effect on stock prices. Partially, Return on Assets has a positive and significant effect on stock prices, while Earnings Per Share has a positive but not significant effect on stock prices at PT Hanjaya Mandala Sampoerna, Tbk. Therefore, the hypothesis proposed by the author is accepted